Metabolic Regulation of Hypoxia-Inducible Factors in Hypothalamus - Du, Dan; Zhang, Yugang; Zhu, Canjun; Chen, Hong; Sun, Jia (Frontiers in Endocrinology, 2021)
The earliest hypoxia-inducible factor (HIF) function was to respond to hypoxia or hypoxic conditions as a transcription factor. Recent studies have expanded our understanding of HIF, and a large amount of evidence indicates that HIF has an essential effect on central regulation of metabolism. The central nervous system’s response to glucose, inflammation, and hormones’ main influence on systemic metabolism are all regulated by HIF to varying degrees. In the hypothalamus, HIF mostly plays a role in inhibiting energy uptake and promoting energy expenditure, which depends not only on the single effect of HIF or a single part of the hypothalamus. In this paper, we summarize the recent progress in the central regulation of metabolism, describe in detail the role of HIF in various functions of the hypothalamus and related molecular mechanisms, and reveal that HIF is deeply involved in hypothalamic-mediated metabolic regulation.